Analysis of Strategies Implemented by AirAsia to Cater to the Covid-19 Effects - Rajesh Kumar Nair; Varsha Ganatra; Karishma Kaur; Daisy Mui Hung Kee; Wan Teng Khoo; Shi Ying Khor; Keshaav Rao; Janhvi Mahajan (Journal of the Community Development in Asia (JCDA), 2021)
During the global pandemic, AirAsia reported an annual loss of RM5.9 billion ($1.4 billion) in 2020. The uncertainty of the COVID-19 outbreak, travel restrictions, and border controls had led to weaker air travel demand, which had impacted AirAsia’s operation badly. This paper depicts how Covid-19 impacted AirAsia and the strategies implemented by AirAsia during the pandemic in the marketing aspects. This paper also focuses on how AirAsia can anticipate a strong recovery in the airline industry while expanding to other industries. In extreme and under pressure circumstances, AirAsia implemented many strategies to cater to the effects of Covid-19. However, other strategies, such as focusing on their business in the food industry, should be expanded throughout Malaysia.